Tokio Marine Indonesia: HR CHALLENGES AMID DIGITAL ECONOMIC SHIFT AND GLOBAL PANDEMIC - Kurnianto, Agustinus Uki; Khomaini, Ahmad; -, Desy; Sari, Dyah Ayu Sekar; Indrajaya, Amelia Naim (Sekolah Tinggi Manajemen IPMI, 2024)
In the context of the COVID-19 pandemic and the accelerating digitalization, Tokio Marine Indonesia (TMI) faces significant challenges in aligning its business strategies with its talent management practices. This study examines the current talent management strategies at TMI and evaluates their effectiveness in supporting the company’s sustainability and growth. The analysis identifies a gap between TMI's traditional human resource approaches and the modern talent management practices necessary to thrive in today's dynamic environment. Key issues include the lack of strategic HR alignment, inconsistent training and development programs, and insufficient succession planning. The study proposes a comprehensive talent management framework that emphasizes global HR directives, robust succession plans, and consistent training programs. The framework aims to enhance TMI’s organizational readiness to address digital economic shifts, business disruptions, and global pandemics by fostering an agile and engaged workforce. Implementing these recommendations is expected to align TMI’s talent management with its broader business strategies, ensuring long-term sustainability and competitiveness.